The Influence of Price Perception, Product Quality, and Service Quality on Purchase Decision at “Bang Ben” Home Steak in Salatiga - Wahyu Astuti; Robby Andika Kusumajaya; Edwin Zusrony (ITB AAS Indonesia Surakarta, 2025)
This study aims to study the influence of price perception, product quality, and service quality on purchasing decisions at “Bang Ben” Home Steak Salatiga. This study uses an associative quantitative research methodology. The subjects of this study were customers of “Bang Ben” Home Steak Salatiga, using a purposive sampling method of 100 respondents. Data were collected using a questionnaire method analyzed with a Likert scale of 1-5. Quantitative analysis was carried out using multiple linear regression analysis and analyzed using the SPSS version 30 application. The results of this study indicate that price perception, product quality, and service quality partially influence purchasing decisions at “Bang Ben” Home Steak Salatiga. The three independent variables have a simultaneous influence on purchasing decisions.